2008
DOI: 10.1016/j.jvs.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Open repair of juxtarenal aortic aneurysms (JAA) remains a safe option in the era of fenestrated endografts

Abstract: Open surgical repair of JAA is associated with low mortality and remains the gold standard. Although 18% had renal complications, only one patient had permanent renal failure. Patients with a combination of physiologic and anatomic risk factors identified on multivariate analysis may benefit from fenestrated endograft repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 27 publications
12
132
5
Order By: Relevance
“…3 Other reports also showed low mortality and technical factors as strong predictors of postoperative renal insufficiency: prolonged operative time, renal ischemic time, clamp position, and left renal vein division. 4, 14 Contrary to those results, we found that by matching the control group, suprarenal aortic cross-clamping had only a slight adverse effect on postoperative renal function.…”
Section: Discussioncontrasting
confidence: 89%
“…3 Other reports also showed low mortality and technical factors as strong predictors of postoperative renal insufficiency: prolonged operative time, renal ischemic time, clamp position, and left renal vein division. 4, 14 Contrary to those results, we found that by matching the control group, suprarenal aortic cross-clamping had only a slight adverse effect on postoperative renal function.…”
Section: Discussioncontrasting
confidence: 89%
“…This patient had JRO, had a prior history of renal failure and was one of the cases also treated with renal revascularization. Some other studies have reported low rates of patients requiring hemodialysis during the postoperative period; 18,25 while others report that up to 10% of patients with prior renal dysfunction subjected to surgery on the juxtarenal aorta required hemodialysis afterwards. 26 West Jr et al 1 reported that 4.1% of patients with CAIO temporarily required hemodialysis during the postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“…While conventional surgery is effective and durable, 15 it is associated with greater invasivity and considerable morbidity and mortality, particularly among patients at high operative risk. Continuous development of materials by the industry has allowed endovascular treatment to become established as an important alternative operating technique for AAA, particularly for patients with favorable anatomy.…”
Section: Discussionmentioning
confidence: 99%